STUFEN THEORY AS A BASIC ANALYSIS OF THE LEGAL STANDING OF THE MINISTERIAL REGULATION AND ITS RELATION TO THE EXECUTION OF THE LOCAL REGULATION - Bachrul Amiq; Yovan Iristian (Yustisia Jurnal Hukum, 2019)
Law is a set of regulations that contain a kind of unity that we understand through a system, as one form of this realization through Article 22A of the 1945 Constitution of the Republic of Indonesia. The legal force binds a regulation in accordance with the hierarchy as referred to in Article 7 of the Law Number 15 of 2019 on the Establishment of Laws and Regulations (hereinafter Law Number 15 of 2019), but in line with Law Number 15 of 2019, it does not recognize the legal standing of the Ministerial Regulation. This research focuses on analyzing and finding answers to questions about the legal standing and characteristics of Ministerial Regulations in the Hierarchy of Statutory Regulations in Indonesia. The research method with a normative juridical approach, prioritizes library research and its implementation in practice. Research specifications are descriptive. The research phase is carried out through library research, collecting secondary data in the form of primary, secondary, and field research materials to obtain primary data as a support. The theory put forward by Hans Kelsen through Stufen Theory and Adolf Merkl’s theory through (Das Doppelte Rechtsantlitz) as a basic analysis to study the legal standing and characteristics of the Ministerial Regulation. In line with the Law 9 of 2015 on the Local Government that Ministerial Regulations are above Provincial, Regency / City Regional Regulations, thus Ministerial Regulations may not conflict with Presidential Regulations and Government Regulations and provide guidelines for Provincial, District / City Regulations in determining the local regulations